Navigating Patient Satisfaction: A Qualitative Insight into Healthcare Delivery during the COVID-19 Pandemic - Shazina Saeed; Manmohan Singhal; Mohd Shannawaz; Mandeep Kumar Arora (Journal of Clinical and Diagnostic Research)
Introduction: The Coronavirus Disease-2019 (COVID-19) pandemic has significantly impacted healthcare delivery systems worldwide, necessitating a re-evaluation of patient satisfaction metrics and experiences within this altered landscape. These changes, while ensuring continuity of care, posed unique challenges, including accessibility, technological adaptation and the maintenance of the quality of patient interactions. In addition, healthcare facilities faced immense strain due to resource allocation, workforce shortages and heightened safety protocols. This unprecedented shift underscores the need to explore how these systemic adaptations have influenced patient satisfaction and shaped their overall healthcare experience in a postpandemic context. Aim: To explore the qualitative aspects of patient satisfaction in healthcare delivery during the COVID-19 pandemic, identifying key factors that influenced patient experiences and perceptions. Materials and Methods: A qualitative research design was employed, utilising an in-depth interviews with patients who accessed healthcare services during the pandemic. The study was conducted in New Delhi, India, among COVID-19 survivors during the period of July 2023 to June 2024. Ethical clearance was obtained from the Institutional Ethics Committee of Amity University (AUUP/IEC/2023/4). Thematic analysis was conducted to identify common themes and insights regarding patient satisfaction. Statistical analysis was performed using the R platform for data visualisation and thematic analysis. Results: The findings revealed several critical themes influencing patient satisfaction, including the accessibility of healthcare services, the quality of communication from healthcare providers, adjustments to telehealth services and the emotional support patients received during their care. Patients expressed both challenges and positive experiences, highlighting the importance of empathy and understanding in healthcare interactions. Conclusion: The study underscores the need for healthcare systems to adapt to evolving patient needs and expectations, particularly in crisis situations like the COVID-19 pandemic. Participants expressed a range of emotions, from frustration to gratitude, highlighting the complexities of navigating healthcare during an unprecedented time. Enhancing communication, increasing accessibility and fostering emotional support are essential strategies to improve patient satisfaction in future healthcare delivery.